Motion Activated Smart Mirror – with Real Time Alerts and Notifications - P, Abinaya S; M, Aanandalakshmi; P, Amy Joanna (IRO Journal on Sustainable Wireless Systems, 2024)
Smart mirrors combine modern technology with traditional home furnishings, creating a harmonious blend of style and function. These cutting-edge gadgets are revitalizing spaces such as restrooms and dressing rooms, transforming them into interactive information hubs. By combining Telegram notifications with motion detection, the newly presented solution improves the functionality of the smart mirror using ESP8266 NodeMCU boards. The integrated solution uses motion sensors and the popular Telegram communication network to instantly notify users on their smartphones whenever motion is detected near the smart mirror. This innovative approach not only simplifies daily life but also enhances security by alerting users to any movement in front of the mirror, whether it’s a family member or a potential intruder. The design and implementation process of this integration, along with its range of applications and implications, are thoroughly examined. From enhancing home automation to strengthening security measures, there are numerous ways to expand the capabilities of these cutting-edge devices and improve user experience by combining motion detection with Telegram notifications in smart mirrors.